A Trinitarian Perspective of Transformational Leadership - Yen Nie Oh (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2022)
The practice of Christian leadership is influenced by the understanding of who God is and His work. The monistic view of God leads to a monistic leadership approach. With the redevelopment of the doctrine of Trinity, many implications are discussed, including in leadership. Christian leaders are exposed to many leadership theories. One of those is Transformational Leadership which is very appealing to Christian leaders. Yet, Christian leaders must develop their understanding and practice of leadership from what they believe about God and His works. This writing will discuss the trinitarian perspectives in developing a Christian foundation for transformational leadership, using literature review on the topic of leadership based on the Trinitarian perspectives, comparing with the transformational leadership theory. Three suggestions are presented to be considered by Christian leaders in practicing transformational leadership from Trinitarian perspectives, shared leadership, mission-centred, and creating space for the Holy Spirit.